SARS-CoV-2 variants of concern are associated with lower RT-PCR amplification cycles between January and March 2021 in France. (December 2021) - Roquebert, Benedicte; Haim-Boukobza, Stéphanie; Trombert-Paolantoni, Sabine; Lecorche, Emmanuel; Verdurme, Laura; Foulongne, Vincent; Burrel, Sonia; Alizon, Samuel; Sofonea, Mircea T.
Highlights: SARS-CoV-2 variants replaced the wild type in France between January and March 2021 The Alpha variant is associated with a 40% increase in transmission on average The mean transmission advantage of the Beta/Gamma variants is estimated to 28% Infections by SARS-CoV-2 Alpha, Beta and Gamma variants exhibit lower Ct values These results suggest these variants have a double viral load compared to wild type Abstract: SARS-CoV-2 variants raise concern regarding the mortality caused by COVID-19 epidemics. We analyse 88, 375 cycle amplification (Ct) values from variant-specific RT-PCR tests performed between January 26 and March 13, 2021. We estimate that on March 12, nearly 85% of the infections were caused by the Alpha variant and that its transmission advantage over wild type strains was between 38 and 44%. We also find that tests positive for Alpha and Beta/Gamma variants exhibit significantly lower cycle threshold (Ct) values.